MODEL PEMBELAJARAN KEWIRAUSAHAAN DALAM UPAYA PENINGKATAN MOTIVASI MAHASISWA UNTUK BERWIRAUSAHA. (Studi Kasus Pada Fakultas Ekonomi Universitas Nurtanio Bandung) - Theresia Marditama (ENSAINS JOURNAL, 2019)
Abstract: The role of the university in motivating students to become young entrepreneurs is very important in an effort to grow the number of entrepreneurs. In an effort to increase student motivation for entrepreneurship, many factors must be considered by the institution. The Faculty of Economics of the University of Nurtanio in this case carried out a beanchmarking with BINUS University which has succeeded in printing young entrepreneurs. The main factor that must be considered is the application of entrepreneurial curriculum learning models that are in accordance with the references of the Higher Education. The purpose of this study is to find out how the learning model has been applied at the current University of Nurtanio, how the learning model applied by BINUS University as a reference institution and how the learning model proposed by researchers to be applied at the Faculty of Economics, University of Nurtanio and what improvements will be made by the University of Nurtanio.Keywords: motivation, entrepreneurship, learning modelAbstract: The role of the university in motivating students to become young entrepreneurs is very important in an effort to grow the number of entrepreneurs. In an effort to increase student motivation for entrepreneurship, many factors must be considered by the institution. The Faculty of Economics of the University of Nurtanio in this case carried out a beanchmarking with BINUS University which has succeeded in printing young entrepreneurs. The main factor that must be considered is the application of entrepreneurial curriculum learning models that are in accordance with the references of the Higher Education. The purpose of this study is to find out how the learning model has been applied at the current University of Nurtanio, how the learning model applied by BINUS University as a reference institution and how the learning model proposed by researchers to be applied at the Faculty of Economics, University of Nurtanio and what improvements will be made by the University of Nurtanio.Keywords: motivation, entrepreneurship, learning model